REPRESENTASI MASKULINITAS DAN FEMINITAS PADA KARAKTER PEREMPUAN KUAT DALAM SERIAL DRAMA KOREA - Eko Rizal Saputra; Hapsari Dwiningtyas Sulityani (Interaksi Online, 2018)
The female characters in Korean dramas are often displayed with emphasis on femininity. The femininity on the text only represents a message of a particular ideology, did not a representation of human being. It could lead to restrictions on women's roles and affirmation of how women should be. Supposedly, women could put themselves on the masculine and feminine side and mass media should be able to bring diversity to the female character. This study aims to see how the representation of masculinity and femininity displayed on a strong female character in the Korean television drama—Strong Woman Do Bong Soon—as an ideal concept for women. The theory that is used in this research was the performance theory of Judith Butler. This study used an approach of discourse analysis on the text of Sara Mills. With this approach, the analytical tools were divided into four structures, including character, fragmentation, focalization, and schemata. The results showed that the character of women brings masculine and feminine values on her. The character displayed with the attribute of femininity through her physical appearance. While in her role, the character displayed two sides, namely masculinity and femininity. Masculinity was in the ability of herself who takes over the role of hero and protector of men. Meanwhile, masculinity and femininity were also seen in the realm of women's work and romance. Fragmentation of a strong female character represented as a body that carries power through her face, chest, waist, hand, leg, and back. Masculinity and femininity were also seen through the position of women in the narrative. Masculinity arised when women act as a subject or Self and femininity exists when women are narrated by other characters or The Other. However, there were also results that show masculinity when the position of women in The Other and femininity on the Self. And in the schemata, masculinity and femininity were shown to shape women's position as a subject. In the social context, the male and female audience tend to interpret the character according to what is displayed. The different meanings influenced by some factors, such as the knowledge and experience of the audience. The presence of masculinity and femininity in a female character here was a form of gender performativity that shows the character was able to escape from dominant performance.